Mycoplasma pneumoniae cytadherence phase-variable protein HMW3 is a component of the attachment organelle. - Stevens, M K (1992)
The subcellular location of the phase-variable cytadherence-accessory protein HMW3 in Mycoplasma pneumoniae has been examined by biochemical and immunoelectron microscopic techniques. Analysis by Western blot (immunoblot) with HMW3-specific antiserum established the presence of this protein within the M. pneumoniae Triton X-100-insoluble fraction or triton shell. Immunogold labeling of Triton-extracted mycoplasmas with affinity-purified antibodies localized HMW3 to the terminal knob on the rodlike extensions of the triton shell, a location that would correspond to the adherence organelle in whole mycoplasmas. Treatment of triton shells with KI resulted in the selective removal of the adherence-accessory proteins HMW1 to HMW4. Analysis of these triton shells by transmission electron microscopy revealed dramatic ultrastructural changes in the filamentous network and core structure. Immunogold labeling of KI-extracted shells reflected the removal of HMW3 from the disrupted tip structure. An examination of ultrathin sections of wild-type cells by transmission electron microscopy following labeling with HMW3-specific antibodies provided further evidence for the nonrandom distribution of HMW3 and its localization to the terminal portion of filamentous cell extensions. Most colloidal gold molecules were associated with the cell interior, but limited peripheral labeling of the terminal region was also observed. Postfixation antibody labeling of whole cells suggested limited exposure of HMW3 on the mycoplasma surface at the tip structure. However, prefixation antibody labeling failed to indicate surface exposure, raising some uncertainty regarding the relationship of HMW3 with the mycoplasma membrane.